Influence of Light Irradiation of Universal Adhesives on the Bonding Effectiveness of Self-adhesive Resin Cements - Kie, NOJIRI; Yoshiyuki, AMARI; Masashi, MIYAZAKI; Toshiki, TAKAMIZAWA; Taketo, OKUWAKI; Akimasa, TSUJIMOTO; Ryo, ISHII; Tatsuya, IIJIMA (The Japanese Journal of Conservative Dentistry, 2020)
Purpose: The purpose of this study was to investigate the influence of light irradiation of universal adhesives on the bonding performance of self-adhesive resin cements based on shear bond strength (SBS) tests and SEM observations of resin/dentin interfaces. Materials and Methods: Three combinations of universal adhesive and self-adhesive resin cement were used: OptiBond Universal/Maxcem Elite Chroma, G-Premio Bond/G-CEM LinkAce, and Scotchbond Universal/RelyX Unicem 2 Automix. Bovine enamel and dentin surfaces were ground with SiC papers, ending at #320 grit. Each universal adhesive was applied to the ground surface in self-etch mode according to the manufacturers’ indications. The treated specimens were divided into two groups, with or without light irradiation of the adhesive applied surface. A stainless-steel metal ring was placed over the bonding area, and the self-adhesive cement was condensed into the ring and light irradiated. Ten specimens per each group were stored in 37°C water for 24 h, and then SBS tests were conducted. Two-way ANOVA followed by Tukey’s honestly significant difference test (α=0.05) was used for analysis of the SBS data. Results: Although SBS value was material dependent for both enamel and dentin, the light irradiation groups tended to show higher SBS values than the non-irradiated groups. In the SEM observations, the adhesive layers with light irradiation were thicker than those without. Conclusion: The results of this study indicated that appropriate light irradiation of universal adhesives may increase the bond performance of self-adhesive resin cements.